2021
DOI: 10.1186/s12883-021-02440-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative cerebrospinal fluid leakage after transsphenoidal surgery for pituitary adenoma: a meta-analysis and systematic review

Abstract: Objective Postoperative cerebrospinal fluid (CSF) leakage represents a challenge even for experienced pituitary surgeons. We aimed to quantitatively synthesize data from studies regarding the risk factors for postoperative CSF leakage after transsphenoidal surgery (TSS) for pituitary adenoma (PA). Methods PubMed, Web of Science, The Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Wanfang database, and VIP database were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
(54 reference statements)
2
9
2
1
Order By: Relevance
“…At present, according to known reports, the incidence of postoperative CSF Leak after endoscopic treatment of pituitary adenoma is between 0.5% and 14% [ 25 , 26 ]. In this study, the incidence of postoperative CSF Leak was 6.79%, close to 5.6% reported in the literature [ 9 , 26 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…At present, according to known reports, the incidence of postoperative CSF Leak after endoscopic treatment of pituitary adenoma is between 0.5% and 14% [ 25 , 26 ]. In this study, the incidence of postoperative CSF Leak was 6.79%, close to 5.6% reported in the literature [ 9 , 26 ].…”
Section: Discussionsupporting
confidence: 85%
“…Although we found in this meta-analysis that age was not a risk factor for CSF Leak, it remains to be further determined because too few articles were included. In our study results, it was determined that BMI, tumor size, reoperation, and occurrence of intraoperative CSF Leak were related factors of postoperative CSF Leak, which were different from 4 related factors of tumor size, adenoma consistency, reoperation, and intraoperative CSF Leak obtained in the meta-analysis [ 9 ], which may be related to different literatures included in the two meta-analyses.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…A recently published large meta-analysis of 34 case-control and cohort studies involving 9144 patients with pituitary adenomas revealed that giant adenoma (<4 cm) was associated with a 3Â increased odds of developing CSF leak versus macroadenoma or microadenoma. 28 In another meta-analysis, larger tumor size and volume were associated with increased complications in general. 9 There has been less consistent demonstration of increased risk of CSF leak in patients with macroadenoma (≥1 cm) versus microadenoma (<1 cm), with one single center study of 108 patients demonstrating no difference in postoperative CSF leak percentage between resection of macroadenomas (14%) and microadenomas (13%) 29 and another identifying lower risk with microadenoma (17%) compared to macroadenoma (34%).…”
Section: Resultsmentioning
confidence: 98%
“…Factoring prominently in the consideration for CSF leak risk is tumor size. A recently published large meta‐analysis of 34 case–control and cohort studies involving 9144 patients with pituitary adenomas revealed that giant adenoma (<4 cm) was associated with a 3× increased odds of developing CSF leak versus macroadenoma or microadenoma 28 . In another meta‐analysis, larger tumor size and volume were associated with increased complications in general 9 .…”
Section: Discussionmentioning
confidence: 99%